Struggling urology trainee: a qualitative study into causes of underperformance. Issue 6 (16th March 2020) - McLeod, Kathryn; Waller, Susan; King, Dennis; Nestel, Debra
Abstract: Background: Urological surgical trainees who underperform are difficult to identify, manage and require significant resources in an already stretched system relying on pro bono supervisors that often have no formal training. While there are commentaries on how to manage underperforming surgical trainees, there is a lack of data detailing the complex reasons for underperformance. It is important to understand the complexities contributing to underperformance so that improved remediation plans can be developed which can better help trainees meet expectations and succeed. Methods: In this qualitative study, individual semi‐structured interviews were conducted with key persons identified as having very high levels of background knowledge and involvement with current underperforming urological surgery trainees. Transcribed interviews were thematically analysed. Results: Ten interviews were conducted, including nine urology consultants and one educational manager. Five themes were identified: underperformance is a small but profound issue; spiral of failure; the changing trainee; lack of insight and under supported supervisors and posts. Conclusion: Causes of underperformance in urology trainees are complex and multifactorial. Behavioural issues were considered the most likely cause, which are also the most challenging to remedy. However, in addition to trainee factors, causative factors related to supervision and training were identified. Addressing all of these issues is paramount if effective remediation of these trainees is to occur. Abstract : In this qualitative study, semi‐structured interviews were conducted to investigate the causes of underperforming urological surgery trainees in Australia and New Zealand. Behavioural issues were considered the most likely cause of trainee underperformance, which are also the most challenging to remedy. However, in addition to trainee factors, causative factors related to supervision and training were identified.